Enhancing endocrine system learning in nursing education: a Ten-Jump model developed at Universitas Negeri Gorontalo - Karim, Cecy Rahma; Nusantari, Elya; Yusuf, Frida Maryati; Solang, Margaretha; Musa, Weny J. A.; Ntobuo, Nova Elysia (Cogent education, 2025)
Teaching the endocrine system in nursing education is challenging due to its complexity. This study introduces a ten-jump learning model for nursing students at Universitas Negeri Gorontalo, using the ADDIE methodology. Incorporating interactive elements and technology, the model aims to enhance comprehension, motivation, and engagement. Evaluated through student assessments, feedback, and learning outcomes, the results showed the model is valid, meets educational standards, and is practical for real-world use. It effectively improves problem-solving skills, promotes independent study, and increases student motivation. The Ten-Jump Model’s success suggests it could be a template for other complex subjects, enhancing educational strategies in nursing and other fields. Further research should explore its broader application to support educational quality and effectiveness.